Application of Statistic Model and Backpropagation Neural Network to Analyzing and Forecasting Hydropower Dam Displacement - Kien Trinh, Bui Thi; Yangxuan, Xiao; Van Doan, Chinh; Xuan Khanh, Do; The Viet, Tran; Dinh Sinh, Mai (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Horizontal displacement of Hoa Binh dam in operation phase was analyzed and then forecasted by using three methods: the multi-regression model (MTR), the Seasonal Integrated Auto-regressive Moving Average (SARIMA) and the Back-propagation Neural Network (BPNN). The monitoring data of the Hoa Binh Dam in 137 periods, including horizontal displacement, time, reservoir water level and air temperature were used for the experiments. The results indicated that all of these three methods could describe the real trend of dam deformation and achieve the required accuracy in short-term forecast up to 9 months. In addition, forecast results of BPNN had the highest stability and accuracy